Land Fragmentation and Occupational Diversification in the Western Terai of Nepal - Dhakal, Bhola Nath (The Third Pole: Journal of Geography Education, 2025)
The study explores the relationship between land fragmentation and occupational diversification in Western Terai, Nepal. It is a universal particularity of all agricultural systems that distresses farmland efficiency and forces adoption of alternate occupations for the subsistence of life. The key objective of this study was to assess the trend of land fragmentation and occupational diversification. This study was based on both qualitative and quantitative methods, including primary and secondary sources of data. It was found that 64.2 percent of the total respondents reported their land fragmentation began after 1983 AD. The main determinants of land fragmentation were inheritance of property and population growth, along with the selling and buying of land, migration, infrastructure development (such as roads and canals), disasters (including floods and erosion), and land plotting. Of the total the respondents, 81.5 percent reported an increase in input cost relative to output due to the scattering of farmland into small, irregular plots, with parcels located an average of 300 to 1,500 meters from farmsteads. This spatial dispersion reduced the priority given to agricultural investment. Consequently, 71 percent of respondents were compelled to seek alternative livelihood activities for their subsistence, driven by land fragmentation, conversion of farmland into built-up areas, and the gradual disappearance of agricultural fields.